2013
DOI: 10.1016/j.livsci.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nutrition on development of gastrointestinal tract of bovine fetus at different stages of gestation

Abstract: This study was developed aiming to evaluate the effects of maternal feed-restriction on development of gastrointestinal tract (GIT) of bovine fetus at different gestational stages. Feed-restricted cows were fed 1.2 times the maintenance level while the control group was fed ad libitum. Pregnant cows were slaughtered at 136, 189, 239, and 269 days of gestation and gastrointestinal tracts of the fetuses were evaluated. No effects of maternal nutrition on body weight (P ¼ 0.17) and body length (P ¼0.13) of the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 14 publications
4
40
0
1
Order By: Relevance
“…However, none of the organs and tissues evaluated in the current study demonstrated this behavior. Similar results were observed by Duarte et al (2013) in fetuses from beef cows that were fed ad libitum or maintenance diets. According to Weaver et al (1991), the phase of rapid growth of the gastrointestinal tract occurs in the third trimester of gestation in species that have a long gestational period.…”
Section: Fetal Viscera and Organ Masssupporting
confidence: 80%
See 1 more Smart Citation
“…However, none of the organs and tissues evaluated in the current study demonstrated this behavior. Similar results were observed by Duarte et al (2013) in fetuses from beef cows that were fed ad libitum or maintenance diets. According to Weaver et al (1991), the phase of rapid growth of the gastrointestinal tract occurs in the third trimester of gestation in species that have a long gestational period.…”
Section: Fetal Viscera and Organ Masssupporting
confidence: 80%
“…However, these studies applied an intensive nutrient restriction that did not meet the energy requirements; in the present experiment, we applied a feed restriction but one that met the energy requirements for maintenance. Moreover, when studying ad libitum-fed or maintenance-fed beef cows, Duarte et al (2013) observed that maternal feed restriction did not affect the development of most fetal gastrointestinal parts, except that the small intestine had an increased surface area as a response to maternal feed nutrition. The lack of effect of FR on the reticulum-rumen mass may be due to the nonfunctionality of these compartments at the fetal stage; theoretically, there is no need to expand the surface area of the stomach to increase nutrient absorption, as this occurs in the small intestine (Duarte et al, 2013).…”
Section: Fetal Viscera and Organ Massmentioning
confidence: 99%
“…Moreover, it has been reported that lambs from ewes submitted to nutritional restriction had better immunoglobulin absorption efficiency during the first hours after birth, while lambs from overnourished sheep had reduced immunoglobulin absorption efficiency (Hammer et al., ). In many of these cases, the foetal intestinal development changes were suggested as adjustments due to a lower or higher maternal ability to produce colostrum according to the feeding level during pregnancy (Swanson et al., ; Hammer et al., ; Duarte et al., ). Information on the direct effects of maternal feeding plan on the foetal intestinal development independent of colostrum production is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario may lead to increased efficiency in nutrient use in the final stage of pregnancy (Bauman and Currie, 1980;Bonnet et al, 2002;Duarte et al, 2013), which may not be sufficient to compensate for the decreased dry matter intake, so the pregnant goat may have a negative energy balance (Bell, 1995). As a consequence, the female starts to mobilize body reserves to meet its energy requirements as well as use alternative substrates to produce propionate for glucose synthesis in the liver (Prezotto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%